2012
DOI: 10.1128/jvi.06375-11
|View full text |Cite
|
Sign up to set email alerts
|

Marked Endotheliotropism of Highly Pathogenic Avian Influenza Virus H5N1 following Intestinal Inoculation in Cats

Abstract: Highly pathogenic avian influenza virus (HPAIV) H5N1 can infect mammals via the intestine; this is unusual since influenza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…Reperant et al . () also demonstrated that route of infection was important for manifestation and cell tropism. In a recent study (Aamelfot et al .…”
Section: Isa Pathogenesismentioning
confidence: 89%
See 1 more Smart Citation
“…Reperant et al . () also demonstrated that route of infection was important for manifestation and cell tropism. In a recent study (Aamelfot et al .…”
Section: Isa Pathogenesismentioning
confidence: 89%
“…; Toffan, Beato, De Nardi, Bertoli, Salviato, Cattoli, Terregino & Capua ; Klenk ), cats (Reperant et al . ; Rimmelzwaan, van Riel, Baars, Bestebroer, van Amerongen, Fouchier, Osterhaus & Kuiken ) and humans (Korteweg & Gu ; Beutel, Wiesner, Eder, Hafer, Schneider, Kielstein, Kuhn, Heim, Ganzenmuller, Kreipe, Haverich, Tecklenburg, Ganser, Welte & Hoeper ). Reperant et al .…”
Section: Isa Pathogenesisunclassified
“…Necrosis of the pancreatic ductal epithelium was observed in ferrets intragastrically infected with HP H5N1 virus (30), and pancreatic postmortem lesions ranging from inflammation to necrosis have also been observed in HP-IAV-infected cats (31,32). Pathological examinations of human fatalities from the H1N1 2009 pandemic also revealed pancreatic lesions in two of six postmortem examinations (33), and in our recent studies using in vitro and ex vivo models, we demonstrated that human cells originating from the exocrine pancreas were infected and killed by LP IAVs (34).…”
mentioning
confidence: 99%
“…58 Whether the latter can be infected following ingestion of HPAIV H5N1 is unknown. Such a route of infection has been demonstrated in ferrets, mice, hamsters and cats [35][36][37]107 and implies that these viruses can survive the acidic environment of the stomach in these species.…”
Section: Do Not Distributementioning
confidence: 90%
“…A digestive route of infection is unusual for influenza viruses in humans and other mammals, yet was demonstrated to occur for HPAIV H5N1 in ferrets, mice, hamsters and cats. [35][36][37]107 Similarly to respiratory transmission of avian influenza viruses, such a route of transmission apparently remains highly inefficient, given its relatively low frequency. Lastly, self-inoculation of the conjunctiva appears to be an important and atypical route of bird-to-human transmission of avian influenza viruses of the H7 subtype, which tends to present preferential tropism for ocular tissues in humans.…”
Section: Routes Of Entry and Transmissionmentioning
confidence: 99%